Perubahan Peran Akuntan di Era Artificial Intelligence dan Robotic Process Automation: Kajian Literatur - Sasti Putri Muda Hasibuan; Nazla Alifia Putri Hadi; Khania Evline Lorenca Br Karo (JURNAL ILMIAH NUSANTARA, 2025)
The development of Artificial Intelligence (AI) and Robotic Process Automation (RPA) has had a substantial impact on the accounting profession, particularly within Public Accounting Firms. These technologies are capable of automating various administrative tasks and enhancing the speed and accuracy of data processing, which in turn shifts the accountant’s focus from routine activities to analysis and the provision of added value for clients. This study aims to describe the changing role of accountants in the context of AI and RPA implementation through a qualitative literature review approach. Data were collected from various reputable journals discussing the application of AI/RPA in auditing and accounting information systems. The findings indicate that AI and RPA offer advantages such as efficiency, improved audit quality, and opportunities for accountants to develop as strategic advisors. However, challenges including initial costs, human resource resistance, ethical concerns, and data security issues require serious attention. In conclusion, the successful adoption of AI and RPA in accounting practices requires accountants’ competency readiness, management support, and clear regulations so that technological transformation can enhance professionalism and the quality of audit services.